2008
DOI: 10.4049/jimmunol.180.1.550
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Rho Kinase by TNF-α Is Required for JNK Activation in Human Pulmonary Microvascular Endothelial Cells

Abstract: TNF‐α induces complex signaling events in endothelial cells (ECs), resulting in gene transcription and increased junctional permeability. This study examined the activation of the RhoA/Rho kinase pathway induced by TNF‐α in primary human pulmonary microvascular ECs and its role in EC responses to TNF‐α. Activation of RhoA was induced by TNF‐α within five minutes. This increase in RhoA activity rapidly decreased, and a late activation of RhoA was induced three hours after TNF‐α treatment. This late but not earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 55 publications
3
65
0
Order By: Relevance
“…Previous studies have demonstrated that TNF-α or glutamate can activate RhoA and Rho kinase [39][40][41]. RhoA is an essential component of the excitotoxicity pathway, and is sufficient to induce the activation of such pathway [42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that TNF-α or glutamate can activate RhoA and Rho kinase [39][40][41]. RhoA is an essential component of the excitotoxicity pathway, and is sufficient to induce the activation of such pathway [42].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated activation of ROCK in response to TNF-␣ that lasts for hours in primary human pulmonary microvascular ECs (15). To begin to evaluate isoform-specific ROCK activation, ROCK1 or ROCK2 was immunoprecipitated from primary human pulmonary microvascular ECs, and ROCK isoform activity was evaluated by an in vitro kinase activity assay using purified MYPT-1 (714-1004) as a substrate.…”
Section: Activation Of Both Rock1 and Rock2 Isoforms In Human Pulmonamentioning
confidence: 99%
“…ECs were treated for 4 h with 10 nM ROCK1 or ROCK2 siRNA or their corresponding control siRNA premixed with 6 g/ml lipofectin (15). The cells were then incubated with normal culture medium for 72 h before experiments.…”
Section: Cells Pharmacologic Inhibitors and Sirnamentioning
confidence: 99%
See 2 more Smart Citations